Analysis of the Feasibility of Education Administration in Elementary Schools - Rosani Djabir; Marwah Marwah; Jamil Jamil (PT Publikasiku Academic Solution, 2026)
Educational administration is the backbone of effective school management. In Pangkajene and Kepulauan (Pangkep) Regency, geographical challenges and the availability of human resources often pose obstacles to meeting administrative standards at the elementary school (SD) level. This study aims to analyze the feasibility of educational administration in elementary schools in Pangkep Regency, covering curriculum administration, student affairs, personnel, facilities and infrastructure, and public relations. This study uses a qualitative descriptive approach with survey techniques. The research subjects included school principals, school administrators, and teachers at 10 sample elementary schools representing mainland and island areas in Pangkep. Data collection was conducted through observation, in-depth interviews, and documentation studies using standard school accreditation instruments. The results of the study show that, in general, the administrative feasibility of education in Pangkep District elementary schools is in the